Evaluasi Akurasi Sensor Suhu Digital untuk Aplikasi Pemantauan Suhu Ruangan Penyimpanan: Studi Indoor dan Outdoor - Setiawati, Aprilia Yogi; Haryanti, Munnik (JURNAL TEKNOLOGI INDUSTRI, 2025)
Accurate temperature monitoring is essential in storage applications that require precise environmental control. This study aims to analyze the accuracy and stability of five digital temperature sensors—DHT11, DHT22, DS18B20, BMP085, and BMP280—by comparing their measurements with a mercury thermometer certified by the Indonesian National Standard (SNI) as the reference. Experiments were conducted in both indoor and outdoor environments using a NodeMCU ESP8266, with repeated measurements performed to evaluate consistency. The analysis was carried out using average measurement deviation and percentage error. The results show that the BMP280 provides the highest accuracy in indoor conditions, with an average deviation of 0.52 °C and a 2.0% error rate, whereas the DS18B20 demonstrates superior accuracy and stability in outdoor conditions, with deviations as low as 0.4 °C in several test points. The DHT11 and DHT22 remain suitable for simple applications with low precision requirements, while the BMP085 exhibits the lowest performance in terms of both accuracy and consistency. These findings offer practical guidance for selecting appropriate temperature sensors based on environmental conditions and application needs.